Construction of large-scale wireless sensor network using ZigBee specification - CHENG Xiao-liang; DENG Zhi-dong (Tongxin xuebao)
A new practicable and feasible networking policy was proposed, called one zone multi-PAN （personal area network[1]）. A two-level abstract model of LS-WSN was proposed. Using BeeStack[2], which was a commercial network- ing protocol that complies with ZigBee specification[3], a prototype system of LS-WSN was constructed. Theoretically, a PAN can support 65 536 nodes. Thus, the size of our LS-WSN could be expanded up to 16 times compared to that of a PAN. Experiences show that the quality of service （QoS） of LS-WSN can be guaranteed. Furthermore, analysis shows that the network management, the data fusion, and the performance can be also improved.